Introduction to Mass communication : - Baran, Stanley J. (McGraw-Hill, 2008)
While encouraging students to be active media consumers, this text gives them a deeper understanding of the role that the media play in both shaping and reflecting culture. Through this cultural perspective, students learn that audience members are as much a part of the mass communication process as are the media producers, technologies, and industries. This was the first, and remains the only, university-level text to make media literacy central to its approach. The updated sixth edition features updated industry statistics, discussion of the affects of recent events on media and media audiences, and coverage of current issues in the media industries.